2015
DOI: 10.1118/1.4926551
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐institutional study to assess adherence to lung stereotactic body radiotherapy planning goals

Abstract: Among the various parameters that were used to evaluate the SBRT plans, the CI100% and CI50% were the most challenging criteria to meet. Although the CSRs of organs at risk were higher among all cases, their proximity to the PTV was a significant factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…The results suggest that the RTOG 0813 R100% constraint levels are set too high to usefully detect sub-optimal plans, as the "tolerance" constraint was only exceeded by 8 of 147 (5%) plans and no submissions exceeded the "minor deviation" constraint. This is better conformity than was reported in a study of 300 lung SBRT plans from 4 centers [34] which found that only 79% of plans achieved the RTOG 0813 "tolerance" constraint (R100% 1.14 ± 0.21 (mean ± SD)). The ROSEL study R100% constraint levels are supported by these data, as they closely match the CtE data median plus 1 SD and median plus 2 SD, although we have chosen to increase some of the ROSEL values slightly to reflect the results and the fact the PDS denominator is the PTV V100%, rather than the PTV volume (which will be cause the PDS value to rise slightly).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…The results suggest that the RTOG 0813 R100% constraint levels are set too high to usefully detect sub-optimal plans, as the "tolerance" constraint was only exceeded by 8 of 147 (5%) plans and no submissions exceeded the "minor deviation" constraint. This is better conformity than was reported in a study of 300 lung SBRT plans from 4 centers [34] which found that only 79% of plans achieved the RTOG 0813 "tolerance" constraint (R100% 1.14 ± 0.21 (mean ± SD)). The ROSEL study R100% constraint levels are supported by these data, as they closely match the CtE data median plus 1 SD and median plus 2 SD, although we have chosen to increase some of the ROSEL values slightly to reflect the results and the fact the PDS denominator is the PTV V100%, rather than the PTV volume (which will be cause the PDS value to rise slightly).…”
Section: Discussioncontrasting
confidence: 47%
“…These data suggest that these constraints are not routinely achievable. The recent study of 300 lung SBRT plans supports this, with 43% exceeding RTOG 0813 R50% "tolerance" and 66% exceeding "minor deviation" levels [34]. The RTOG 0813 constraints in general appear to be mis-matched to the gathered data, with the R100% constraints being too lax (particularly for larger PTVs), and the R50% constraints being Table 1 Conformity metrics for all 147 plans submitted through the CtE programme, split by PTV V100% volume range.…”
Section: Discussionmentioning
confidence: 92%
“…While lung SBRT has been demonstrated to be highly successful in achieving local control, the use of more potent (and, arguably more effective) SBRT fractionation schema as well as the administration of SBRT to more centrally-located lesions are limited in practice because of potential toxicity to surrounding tissues. 25,26 The applications of SBRT can be potentially further expanded by creating treatment plans with improved OAR-sparing and, hence, lowered toxicity. The 4D planning concept can be independently applied to most commonly deployed treatment delivery techniques, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter study, they found significant differences for target coverage and OAR sparing due to different optimization strategies selected by the planners. Another multi-institutional study evaluated dosimetric parameters for SBRT of lung lesions and how much the guidelines provided in the literature are being successfully implemented in a variety of clinics [ 37 ]. They analyzed PTV coverage and conformality of their treatment plan and found that and the conformality index of 50 % was the most difficult to meet depending on tumor size and location.…”
Section: Discussionmentioning
confidence: 99%